Risk assessment of aluminum in drinking water between two residential areas - Mohamed Ali, Dzulfakar; Mohd Sham, Shaharuddin; Amiruddin, Abd Muhaimin; Ismail, Syazwan Aizat (MDPI, 2011)
A cross-sectional study was conducted at Sungai Lembing (SL) and Bukit Ubi (BU), Kuantan, Malaysia. The main objectives of this epidemiological study were to determine the aluminum concentration in drinking water, to compare with the government standard and to perform health risk assessment prediction among respondents from these two residential areas. A total of 100 respondents were selected from the study areas based on a few inclusive and exclusive criteria. Two duplicates of treated water samples were taken from each respondent's house using a 200 mL high-density polyethylene (HDPE) bottle and 0.4 mL (69%) pure concentrated nitric acid added as preservative. Aluminum concentrations were analyzed using Lambda 25 UV/V spectrophotometer. The result showed that the mean concentration of aluminum in drinking water from SL was 0.11 ± 0.0634 mg/L and 0.12 ± 0.0462 mg/L for BU. The mean value of Chronic Daily Intake (CDI) in SL (0.0035 ± 0.0028 mg/kg/day) was lower compared to BU (0.0037 ± 0.0021 mg/kg/day). The Hazard Index (HI) calculation showed all respondents had HI less than 1. In conclusion, there was unlikely potential for adverse health effects from aluminum intake in drinking water. However, it was necessary for some action to be taken in order to reduce aluminum levels found in drinking water in both locations.